Market power of the Japanese non-GM soybean import market - Yamaura, Koichi (Kansas State University, 2008)
Globally, the majority of countries now use genetically modified (GM) soybeans to produce oil and meal for livestock and human consumption. Japan, however, uses only Non-GM soybeans for direct human consumption of which more than 80% are imported from the U.S., Canada, and China. This research used the inverse residual demand model to estimate a two-country partial equilibrium trade model to test the existence of market power in the Japanese Non-GM soybean import market. The two-country partial equilibrium trade model incorporated the U.S. residual Non-GM soybean supply for Japan, the Japanese residual demand for U.S. Non-GM soybeans, and the equilibrium condition, where the U.S. residual Non-GM soybean supply equals the Japanese residual Non-GM soybean demand. Monthly data from January 2003 to December 2007 were used for the analysis. Empirical results indicated that U.S. Non-GM soybean exporters have stronger market power than Japanese Non-GM soybean importers. The results also indicate that Japanese consumers are willing to pay higher prices for soybeans, tofu, natto, miso, and other all soy food products.
Keywords: Non-GM Soybean; Market Power; Japanese Soybean Import Market; Two-Country Partial Equilibrium Trade Model; U.S. Non-GM Soybean; Japanese Soy Foods; Economics, Agricultural (0503)